Enhancing Fifth Grade Students’ Character Values through the Value Clarification Technique (VCT) in Civic Education Learning - Jannah, Miftahul; Irawan, Ady; Hidayat, A. Gafar (Lectura : Jurnal Pendidikan, 2025)
The increasing prevalence of moral and social issues among elementary students highlights the urgent need to strengthen character education. This study explores the strategic role of civic education in fostering core values such as religiosity, honesty, discipline, responsibility, and tolerance among fifth-grade students at SDN Inpres Pandai. Utilizing a Classroom Action Research (CAR) design conducted over two cycles, the study implemented the Value Clarification Technique (VCT) as an instructional intervention. The research involved 31 students and followed the stages of planning, implementation, observation, and reflection. Data were collected through observation checklists, interviews, document analysis, multiple-choice tests, teacher assessments, and student self-reflection instruments. The results indicated substantial improvements across all five character dimensions. Students’ initial mastery levels, which ranged from 54.8% to 74.2%, increased to between 83.9% and 90.3% following the intervention, placing all participants within the “very well developed” category. The VCT approach enabled students to engage critically with real-life moral dilemmas, express their values, and reflect on ethical decision-making. These outcomes demonstrate the effectiveness of VCT in enhancing students’ moral reasoning and ethical behavior, aligning with the goals of Indonesia’s Merdeka Curriculum and the Pancasila Student Profile. In conclusion, the potential of VCT as a valuable pedagogical tool in promoting character education at the primary level.